Response of tillage methods on yield of wheat (Triticum aestivum) cultivars - SAINI, ANKIT; MANUJA, SANDEEP; KUMAR, SURESH; UPADHYAY, R G; SAHOO, CHINMAYA (The Indian Journal of Agricultural Sciences, 2025)
The present experiment was conducted during winter (rabi) seasons of 2019–20 and 2020–21 at Chaudhary Sarwan Kumar Himachal Pradesh Krishi Vishvavidyalaya, Palampur, Himachal Pradesh, to assess the impact of tillage and farming practices on the crop yield and yield attributes of three wheat (Triticum aestivum L.) cultivars. Two-year results show that conventional tillage produced significantly higher grain yields (4,469 kg/ha), straw yields (6,257 kg/ha), and biological yields (10,726 kg/ha) than natural farming treatment, which produced lower grain yields (1,646 kg/ha), straw yields (2,597 kg/ha), and biological yields (4,242 kg/ha). While the natural farming treatment had much lower values of wheat yield attributes, the conventional tillage treatment, which was followed by the reduced tillage treatment, had significantly higher values. Among the cultivars assessed, HPW 368 had noticeably higher grain yield (3,714 kg/ha), straw yield (5,415 kg/a), and biological yield (9,128 kg/ha) values. This was because the variety's yield attributes were much greater. According to the results of this study, the wheat crop produced more under conventional farming conditions, and HPW 368 was the cultivar that performed the best out of all those evaluated.